2017
DOI: 10.1111/glob.12179
|View full text |Cite
|
Sign up to set email alerts
|

Transnational activism in support of national protest: questions of identity and organization

Abstract: In this article, I consider the question of whether transnational activism supporting national protest attains a cohesive collective identity on social media while remaining localized organizationally. I examine a corpus of social media data collected during two months of rolling protests in 2013 against the largest proposed open‐cast gold mine at Roşia Montană, Romania, which echoed among Romanian expatriates. A network text analysis of the data supplemented with interview findings revealed concerns with prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 45 publications
(32 reference statements)
0
13
0
Order By: Relevance
“…While the #rezist event pages may have been a vehicle for local communication, the singular focus of the protests, on fighting corruption in Romania, would have acted as an incentive for disparate local actors to act cohesively (Mercea, 2018). If Facebook event pages were used to that end, structural brokers would have been instrumental to engendering such coherence despite any focus on local events.…”
Section: Research Questions and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…While the #rezist event pages may have been a vehicle for local communication, the singular focus of the protests, on fighting corruption in Romania, would have acted as an incentive for disparate local actors to act cohesively (Mercea, 2018). If Facebook event pages were used to that end, structural brokers would have been instrumental to engendering such coherence despite any focus on local events.…”
Section: Research Questions and Hypothesesmentioning
confidence: 99%
“…That year, a wave of solidarity protests erupted in more than 30 cities worldwide in support of a long-running environmental protest against the largest proposed open-cast gold mine in Europe, in North-Western Romania. Weekly rolling demonstrations ran for 3 months simultaneously in the country and abroad bringing to light a transnational network of Romanian expatriates who seized on social media – particularly public Facebook event pages – to organize demonstrations locally and coordinate cross-nationally (Mercea, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Support network perspectives have been incorporated in social movement studies, and scholars have found that transnational activism can support national protests to attain a cohesive collective identity. Internet and social media efficiently spread information, shape narratives and mobilize specific identities (Mercea, 2018; Cheng & Yuen, 2020). Networked communications connect multiple actors and groups striving for a collective voice of renewed solidarity to confront governments or enterprises (Lee et al., 2021; Werbner, 2002; Yam, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…ILGA World, the International Lesbian, Gay, Bisexual, Trans and Intersex Association established in 1978), not least through increasing transnational migration (Ayoub & Bauman, 2019;Della Porta & Tarrow, 2004). Similar transnational activism connecting the local and the global has been discussed in recent research, too, yet the transnational connections tend to be limited to the same ethnic or national group (Koinova & Karabegovič, 2017;Li & Fung, 2021;Mercea, 2017). Such an approach does not reflect ongoing debates on the diversification of transnational communities themselves and the critique on the ethnofocal lens (Meissner & Vertovec, 2015;Yamamura & Lassalle, 2020).…”
Section: Introductionmentioning
confidence: 97%